Answer:
0=0
Explanation:
Simplifying
-5(x + -7) = 35 + -5x
Reorder the terms:
-5(-7 + x) = 35 + -5x
(-7 * -5 + x * -5) = 35 + -5x
(35 + -5x) = 35 + -5x
Add '-35' to each side of the equation.
35 + -35 + -5x = 35 + -35 + -5x
Combine like terms: 35 + -35 = 0
0 + -5x = 35 + -35 + -5x
-5x = 35 + -35 + -5x
Combine like terms: 35 + -35 = 0
-5x = 0 + -5x
-5x = -5x
Add '5x' to each side of the equation.
-5x + 5x = -5x + 5x
Combine like terms: -5x + 5x = 0
0 = -5x + 5x
Combine like terms: -5x + 5x = 0
0 = 0
Solving
0 = 0
Couldn't find a variable to solve for.
This equation is an identity, all real numbers are solutions.